Analisis Manajemen Risiko Pada Aplikasi Pegadaian Digital Service Menu Tabungan Emas Menggunakan ISO 31000:2018 - Kwee Mey Linda Lole; Evi Maria (Universitas Budi Darma, 2022)
The purpose of this research is to analyze information technology risk management on the implementation of the gold savings menu on Pegadaian Digital Service (PDS) application in PT Pegadaian Waingapu Branch using the ISO31000:2018 framework. The risk management process is carried out starting from the communication and consultation stage, the context setting stage, the risk assessment stage, consist of risk identification, analysis and evaluation, as well as the risk treatment stage. The result of this research found that there are 23 possible risks in gold saving menu PDS application. Of the 23 possible risks, there is one risk that has a high risk level, namely data leakage, six risks at the medium level and 16 risks at the low level. This research also provides recommendations to PT Pegadaian Waingapu Branch management for risks treatment that arise from the implementation process of the gold savings menu PDS application. The results of risk management analysis for gold savings menu in PDS application from this research are documented in form of a risk register to help the management in managing risks.